Post‐Tonsillectomy Ibuprofen: Is There a Dose‐Dependent Bleeding Risk?. (24th September 2021) - Losorelli, Steven D.; Scheffler, Patrick; Qian, Z. J.; Lin, Hung‐Fu C.; Truong, Mai Thy
Abstract : Objectives/Hypothesis: Post‐tonsillectomy hemorrhage (PTH) is a potentially life‐threatening complication. A recent meta‐analysis suggests that ibuprofen may increase the risk of PTH. The aims of this study were to 1) re‐evaluate the effect of ibuprofen on PTH given additional recent evidence and 2) to evaluate a potential dose effect of ibuprofen. Study Design: Meta‐analysis and meta‐regression; single‐institution retrospective review. Methods: We conducted a systematic review of the literature and a meta‐analysis of 12 studies comparing postoperative ibuprofen analgesia to non‐nonsteroidal anti‐inflammatory drug (NSAID) controls. Next, we performed a meta‐regression analysis to assess for an effect of dose, if any, on rates of PTH. Five studies specifying a dose of 5 mg/kg (828 patients, 1, 411 controls) and 7 studies using 10 mg/kg (5, 633 patients, 7, 656 controls) were included. We then conducted a novel single‐institution, retrospective review of data for 1, 046 patients prescribed intermediate‐dose 7.5 mg/kg ibuprofen. Results: Ibuprofen was not associated with an increased rate of PTH (log odds ratio [OR], 0.21; 95% confidence interval [CI] −0.15, 0.57). Meta‐regression showed that ibuprofen dose (5 and 10 mg/kg) did not have a statistically significant effect on PTH (OR, 1.32; 95% CI 0.30, 5.84). Uncontrolled, aggregate rates of PTH across all studies were 2.29% (N = 828) for 5 mg/kg and 4.65% (N = 5, 633) for 10 mg/kg dosing. The rate of secondary hemorrhage in patients prescribed 7.5 mg/kg ibuprofen was 3.10% (N = 1, 046). Conclusion: We found no statistically significant increased risk of PTH when ibuprofen is prescribed at the low or high range of commonly used clinical dosages, compared to a non‐ibuprofen regimen. Further studies with less heterogeneity are needed to determine if there is a clinically relevant dose‐dependent difference in PTH with ibuprofen. Level of Evidence: 3 Laryngoscope, 132:1473–1481, 2022